2015
DOI: 10.1002/2014tc003590
|View full text |Cite
|
Sign up to set email alerts
|

Extension across the Laptev Sea continental rifts constrained by gravity modeling

Abstract: The Laptev Shelf is the area where the Gakkel Ridge, an active oceanic spreading axis, approaches a continental edge, causing a specific structural style dominated by extensive rift structures. From the latest Cretaceous to the Pliocene, extension exerted on the Laptev Shelf created there several deep subsided rifts and high-standing basement blocks. To understand syn-rift basin geometries and sediment supply relationships across the Laptev Shelf, accurate extension estimates are essential. Therefore, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…In the Laptev Sea, the Late Cretaceous and early Cenozoic extension preceded the opening of the Eurasian oceanic basin and formed a vast rift system (Drachev et al, 1998;Franke et al, 2001;Drachev, 2011). As shown recently by Mazur et al (2015), Drachev and Shkarubo (2017) and Drachev et al (2017), the thinning of the continental crust beneath the U L ' may have resulted in a complete rupture of the continental crust and upper mantle exhumation.…”
Section: Geological Setting and Main Crustal Domains Of The Esasmentioning
confidence: 94%
“…In the Laptev Sea, the Late Cretaceous and early Cenozoic extension preceded the opening of the Eurasian oceanic basin and formed a vast rift system (Drachev et al, 1998;Franke et al, 2001;Drachev, 2011). As shown recently by Mazur et al (2015), Drachev and Shkarubo (2017) and Drachev et al (2017), the thinning of the continental crust beneath the U L ' may have resulted in a complete rupture of the continental crust and upper mantle exhumation.…”
Section: Geological Setting and Main Crustal Domains Of The Esasmentioning
confidence: 94%
“…However, by using seismically constrained boundaries and geologically reasonable densities for the modelled bodies down to the Moho, we are able to minimize the number of possible outcomes. The range of rock densities (Table 1) is adopted from a previous modelling study by Mazur et al (2015) as well as being calculated from seismic interval velocities using a Nafe-Drake formula (Ludwig et al 1970;Brocher 2005).…”
Section: Gravity Modellingmentioning
confidence: 99%
“…The first attempt to constrain the amount of crustal stretching across the LRS with the use of 2D gravity modelling and 3D gravity inversion was published by Mazur et al (2015). They showed that the amount of crustal extension in the central and northern parts of the Ust' Lena Rift Basin reached 430 and 500 km, respectively, and resulted in both the complete elimination of the continental crust and mantle exhumation beneath this hyperextended basin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Среди них прежде всего следует отметить проблему, связанную с объяснением отсутствия регулярных линейных магнитных аномалий в самом южном сегменте Евразийского бассейна. В некоторых публикациях практически весь набор кайнозойских магнитных аномалий по инерции произвольно протягивается до континентального склона Лаптевоморской окраины в попытке определить таким образом положение полюса Эйлера при открытии Евразийского бассейна [9]. В этой связи очевидно и то, что на подходе к южной оконечности бассейна в ряде мест линейные магнитные аномалии теряют субпараллельную ориентировку и смыкаются.…”
Section: некоторые проблемы тектоники исследуемого района арк тикиunclassified